Resistance training for the prevention and treatment of chronic disease - Ciccolo, Joseph T.; Kraemer, William J., 1953- (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2014)
'Resistance training is a form of strength training in which each effort is performed against a specific, opposing force generated by resistance. Increasing evidence-based research highlights the importance of not only aerobic exercise, but resistance training in the prevention, management, and treatment of many chronic conditions. This book presents research on the benefits of resistance training for chronic diseases/disorders. Chapters cover resistance training to treat cardiovascular disease, metabolic diseases, cancer, orthopedic diseases, and neuromuscular disorders'--
Introduction / Joseph T. Ciccolo and William J. Kraemer -- Resistance training program variables and guidelines / Nicholas A. Ratamess -- Resistance training for cardiovascular disease / Randy W. Braith and Joseph C. Avery -- Resistance exercise interventions across the cancer control continuum / Brian C. Focht, Alexander R. Lucas, and Steven K. Clinton -- Effects of resistance training on insulin sensitivity and glycemic control: potential role in the prevention of type 2 diabetes / Christian K. Roberts -- Resistance training in chronic renal failure / Birinder S. Cheema and Danwin Chan -- Beneficial effects of progressive resistance training in multiple sclerosis / Lara A. Pilutti and Robert W. Motl -- Resistance training for Parkinson's disease / Brian K. Schilling and Kelley G. Hammond -- Resistance training for fibromyalgia / J. Derek Kingsley -- Resistance training after stroke / Richard W. Bohannon -- Effects of resistance training on depression and anxiety / Shawn M. Arent and Brandon L. Alderman -- Progressive resistance training for individuals with chronic obstructive pulmonary disease / Simone D. O'Shea and Nicholas F. Taylor -- Benefits of resistance training for HIV/AIDS / Jacob J. van den Berg and Joseph T. Ciccolo -- Resistance training for individuals with orthopedic disease and disability / Mark D. Faries -- Resistance training for older adults / Michael G. Bemben, Christopher A. Fahs, Jeremy P. Loenneke, Lindy M. Rossow, and Robert S. Thiebaud -- Resistance training for children and adolescents / Avery D. Faigenbaum.
Includes bibliographical references and index.
Keywords: Chronic Disease -- therapy; Resistance Training